Severe tremors induced by tiletamine e-cigarette and alcohol use: a case report - Bojie Zhou; Bojie Zhou; Shanghao Yang; Shanghao Yang; Xiafeng Zhou; Xiafeng Zhou; Qian Chen; Qian Chen; Ewen Tu; Ewen Tu; Bo Zhang; Bo Zhang; et al. (Frontiers in Psychiatry)
Background and objectivesPolydrug use has caused serious harm to public health, especially involving novel psychoactive substances. Tiletamine, an N-methyl-D-aspartate receptor (NMDAR) antagonist commonly used as a veterinary anesthetic, has recently emerged in China as an additive in e-cigarettes. However, the long-term impacts of tiletamine and its combined use with other substances remain poorly understood. This case report aims to provide further insight into the clinical manifestations and treatment of tiletamine abuse, particularly focusing on the tremors induced by polydrug use.Case presentationThe patient had five years of intermittent alcohol use and five months of etomidate abuse. After combining tiletamine for two months, he was repeatedly hospitalized due to coarse tremors, poor sleep and appetite. Based on his substance use pattern and related outcomes, he was diagnosed with phencyclidine use disorder. Initially, intravenous diazepam (20 mg/day) effectively alleviated the tremors. During the second hospitalization, the same dose took longer to take effect, and by the third hospitalization, the dose was increased to 30 mg/day without reducing the tremors. Therefore, primidone was added and gradually titrated to 50 mg/day. The patient’s tremors began to improve by the eighth day and significantly diminished by the tenth day. As we gradually replaced diazepam with lorazepam, the patient insisted on discharge.ConclusionsPolydrug users, particularly those using NMDAR antagonists and gamma-aminobutyric acid type A receptor (GABA-AR) agonists, may be at increased risk of developing tiletamine dependence, with more severe consequences due to cross-addiction. The combination of alcohol and tiletamine could exacerbate neuroexcitotoxicity during withdrawal, potentially contributing to severe tremors. The successful management of tremors with a combination of neuroinhibitory therapies suggested an effective strategy for complex cases. Further studies are needed to better understand the long-term impacts and risks of tiletamine dependence.